State-of-art in surgical treatment of dissecting posterior circulation intracranial aneurysms - Balik, Vladimir; Yamada, Yasuhiro; Talari, Sandeep; Kei, Yamashiro; Sano, Hirotoshi; Suyama, Daisuke; Kawase, Tukasa; Takagi, Kiyoshi; Takizawa, Katsumi; Kato, Yoko (Neurosurgical review, 2018)
Vertebrobasilar (VB) intracranial dissecting aneurysms (IDAs) pose difficult therapeutic issues and are especially among the most difficult to manage surgically. There are, however, some cases where selective aneurysm obliteration by endovascular approach is impossible or is associated with an unacceptable risk of morbidity. This is particularly true when the aneurysm is dissecting, giant, or has a large neck. In such cases, surgical treatment may be the only alternative. Optimal management of these lesions is therefore challenging and treatment decisions have to be made on a case-by-case basis. Ideal treatment should be a complete surgical excision of the lesion; however, this procedure might only be possible after distal and proximal vessel wall occlusion which might not be tolerated by the patient depending on the location of the aneurysm. Therefore, formulation of recommendations concerning the surgical strategy remains still difficult due to inconsistency of surgical outcomes. The literature describing surgical strategy of VB IDAs is varying in quality and content, and many studies deal with only a few patients. In the presented review, the authors summarize the current knowledge on the incidence, pathogenesis, clinical presentation, and diagnostic procedures with special emphasis on surgical treatment of IDAs in posterior circulation.
Keywords: Risk Factors; retrospektivní studie; mozkový krevní oběh; Humans; lidé; disekce aorty; Retrospective Studies; Cerebral Angiography; mozková angiografie; Treatment Outcome; Embolization, Therapeutic; výsledek terapie; disekce arteria vertebralis; Aortic Dissection; terapeutická embolizace; intrakraniální aneurysma; Cerebrovascular Circulation; Intracranial Aneurysm; rizikové faktory; Vertebral Artery Dissection